Antibacterial potential of lichen extracts and insights into their diversity in selected areas in Manila, Philippines - Jamie Adrienne C. Fellores, Jaime II C. Jabon, Jasper K. Naguit, Ken Joshua S. Santos 4 0 16; 5
ABSTRACT: This study investigated the antibacterial properties of acetone extracts from lichen species, namely, Lepraria incana, Lepraria finki and Physcia caesia, collected from selected areas in Manila, specifically against the gram-positive bacterium Staphylococcus aureus and the gram-negative bacterium Escherichia coli. The research aimed to explore lichen diversity and their potential medical applications by assessing the taxonomic diversity, coverage, and frequency of lichen species found in Intramuros, Rizal Park, and Paco Park, and by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of each lichen crude extract. The study employed both paper disk diffusion assays and tube dilution methods to evaluate antibacterial efficacy. Major findings revealed that all lichen extracts demonstrated antibacterial activity, with the greatest zone of inhibition (ZOI) observed for extracts of L. finkii against S. aureus and of P. caesia against E. coli. Statistical analysis using two-way ANOVA showed significant differences in antimicrobial activity among different lichen species and locations. The study concluded that the identified lichen species, primarily from the genera Lepraria and Physcia, exhibited significant antibacterial properties, particularly against gram-positive bacteria, highlighting their potential as sources of novel antimicrobial agents. Further recommendations included broadening the scope to include a wider range of bacterial species, employing molecular techniques for species identification, comparing crustose and foliose species, and isolating specific metabolites responsible for antibacterial activity. Keywords: Antimicrobial activity, Lepraria incana, Lepraria finkii, Physcia caesia, Minimum bactericidal concentration, Minimum inhibitory concentration, Zone of inhibition
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2